The Telescope Calibration of the Imaging X-Ray Polarimetry Explorer - Brian D. Ramsey; Jeffery K. Kolodziejczak; Wayne H. Baumgartner; Nicholas E. Thomas; Stephen D. Bongiorno; Philip Kaaret; Stephen L. O’Dell; Allyn Tennant; Martin C. Weisskopf; Sergio Fabiani; Fabio Muleri; Paolo Soffitta; et al. (The Astronomical Journal)
Fifty years after the very first sounding rocket measurement of cosmic X-ray polarization, the Imaging X-ray Polarimetry Explorer (IXPE) mission has effectively opened a new window into the X-ray sky. Prior to launch of IXPE, an extensive calibration campaign was carried out to fully characterize the response of this new type of instrument. Specifically, the polarization-sensitive detectors were intensively calibrated in Italy, where they were developed and built. The X-ray optics, which collect and focus X-rays onto the detectors, were built and calibrated in the USA. A key question was whether the telescope (optics + detectors) calibrations could be synthesized from the individual component calibrations, avoiding time consuming and costly end-to-end calibrations for a flight program with a fixed schedule. The data presented here are from a calibration of the flight spare telescope utilizing the flight spare detector and flight spare mirror assembly combined. These data show that the presence of the mirror module does not affect the polarization response of the detectors (within the required calibration accuracy) and that the angular resolution of the telescopes could be accurately determined. Thus, the original extensive stand-alone ground calibration data of all the flight detectors and all the flight optic can be utilized in full to derive the flight telescopes calibrations.